FAKTOR LAKA LANTAS DALAM SENI LUKIS REALIS KONTEMPORER - RONALD SAPUTRA, Drs. Ismanadi Uska, Yasrul Sami, S.Sn, M.Sn (Serupa The Journal of Art Education, 2013)
Factor in a traffic accident Contemporary RealisKontemporert Art thesis. Arts Education, Faculty ofLanguage and Arts, State University of Padang. There arethree main factors that cause accidents. The first is thehuman factor, both the vehicle and the third factor is thefactor of the road. This is the final work destination (1).Increase the sensitivity of the author in response toconcern for traffic accidents and poured it into thepainting, (2). Adding references and knowledge of thetraffic accident. The title of the work from then lakafactors including Broken Ban, Wild Racing, BreakingBoundaries, Disastrous hole, Street Parking In theshoulder, street Ba phone Juolai. Kata kunci: Faktor Lakalantas, Seni Lukis Realis Kontemporer